O Lago da represa retiro baixo, Rio Paraopeba - MG: uma abordagem químico- ambiental três anos após o rompimento em Brumadinho - Barbara Tharyni Rodrigues Sousa (2022)
The composition of a water body has characteristics that represent indicators of the health of the ecosystem. In the basin of the São Francisco River, during the Paraopeba River, there is the Retiro Baixo Hydroelectric Power Plant, which was affected by the environmental accident caused by the rupture of the Brumadinho dam. This work aims to evaluate the water and sediment situation in the dam 3 years after the Rio Paraopeba disaster. Sampling was carried out at 65 points for water and 15 points for sediment and took place in October/2021. Non-conservative physicochemical parameters were determined in situ: temperature, hydrogen potential, electrical conductivity, dissolved oxygen, total dissolved solids, oxidation-reduction potential. In the collected water, the concentration of the following metals was measured in the laboratory: Fe; Al, Mg, Ca, Mn, Cr, Cu, Co, Cd, Ni, Pb, Zn, Ba, Ti. In the fine fraction of the sediments. The sediments were (<0.063mm), after partial extraction with HNO3, (USEPA-3051a method) the concentration of the following metals was obtained: Fe; Al, Mg, Ca, Mn, Cr, Cu, Co, Cd, Ni, Pb, Zn, Ba, Ti by ICP-OES. The EPT's contents were compared with values of environmental legislation for water (CONAMA 357/2005), and sediment (CONAMA 454/2012). In general, the dam presents appropriate environmental quality values, with small points of attention that may indicate local sources of pollution, however the region presents good conditions in that environment.